The IARC Perspective on Cervical Cancer Screening. Issue 3 (March 2022) - Bouvard, Véronique; Wentzensen, Nicolas; Mackie, Anne; Berkhof, Johannes; Brotherton, Julia; Giorgi-Rossi, Paolo; Kupets, Rachel; Smith, Robert; Arrossi, Silvina; Bendahhou, Karima; Canfell, Karen; Chirenje, Z. Mike; et al.
Abstract : (Abstracted from N Engl J Med 2021;385:1908–1918) In May 2018, the World Health Organization (WHO) called for the elimination of global cervical cancer as a major public health priority, with a 2-pronged approach focusing on effective vaccination against human papillomavirus (HPV) and the screening for and treatment of early cervical cancer. Cervical cancer is considered largely preventable through these programs; however, it continues to be disproportionately prevalent in countries with the lowest values on the Human Development Index.